Hubungan Pola Asuh Orangtua dengan Kejadian Pelecehan Seksual - Nurkhasanah, Nurkhasanah; Sary, Lolita; Aryastuti, Nurul (LPPM Hang Tuah Pekanbaru, 2024)
Sexual harassment is the misuse of the relationship between a woman and a man that harms one of the parties. Based on data reports on cases of violence in Lampung Province in 2022, there were 41% cases of sexual harassment. One of the factors that influence the incidence of sexual harassment is parenting style. The purpose of this study was to determine the relationship between parenting style and the incidence of sexual harassment at SMP X Pesisir Barat Regency in 2023. This type of research is quantitative with a cross-sectional design. The population in this study were all class VIII teenagers at SMP X Pesisir Barat District with a total of 150 people. The sampling technique used is total sampling. Data collection techniques using a questionnaire. Data analysis using chi-square. The results of this study indicated that there were 38 (25.3%) respondents who had experienced sexual harassment and 112 (74.7%) respondents who had never experienced sexual harassment. The results of the bivariate analysis showed that there was a relationship between authoritarian parenting styles (p=0.001; 0.008), democratic fathers (p=0.024), negligent parenting (p=0.039; 0.029), and spoiling parents (p=0.042; 0.045). with incidents of sexual harassment. Meanwhile, the mother's democratic parenting style (p=0.791) was not related to the incidence of sexual harassment. It is hoped that health workers can be educated about boundaries in sexuality so that adolescents understand boundaries that can be guarded and considered private.